The non-culpability of moral ignorance - Long, Veronica Kai Hui (Nanyang Technological University, 2020)
Are the people who engaged in immoral practices that are believed to be moral in their society to be held morally responsible for their actions? Gideon Rosen’s argument for the Parity Thesis of Ignorance follows one of the most influential philosophical views about cultural impediments to moral responsibility, that is, the upbringing of a person in certain culture can render one unable to know that some acts are wrong. The paper will look at some of the objections the Parity Thesis faces.